Chinese Multidisciplinary Expert Consensus on Orphan/Anticopper Drugs and Other Non-drug Management of Hepatolenticular Degeneration - Yang, Ren-Min; Feng, Tao; Cai, Wei; Yu, Xu-En; Wang, Gang; Han, Yong-Zhu; Fan, Cun-Xiu; Xia, Qiang; Chen, Hai-Bo; Wang, Xiao-Ping (Current Neuropharmacology, 2025)
BackgroundThis study aims to guide the diagnosis and treatment of hepatolenticular degeneration (also named Wilson's disease, WD) and aid multidisciplinary clinicians in making reasonable and personalized treatment regimens.ObjectivesThe authors aim to establish a systemic structure for Chinese Multidisciplinary Expert Consensus on Diagnosis and Treatment of Hepatolenticular Degeneration.MethodsWe collaborated with experts from relevant branches of the Chinese Medical Association and multiple disciplines, along with statistical experts, to formulate this consensus. It is based on advancements in basic and clinical research on Wilson's disease, both domestically and internationally.ResultsIt mainly consists of clinical manifestations, diagnosis, differential diagnosis, management, and prognosis in the context of Multi-Department treatment (MDT) in China.ConclusionThis Chinese consensus incorporates four decades of institutional experience with thousands of Chinese Wilson’s disease (WD) inpatients, as well as decades of international inpatient cases from East to West. It is hoped that this consensus will garner broader attention from clinicians worldwide.
Keywords: Multidisciplinary expert